Serum folate levels and risk of metabolic dysfunction-associated steatotic liver disease: results from a cross-sectional study and Mendelian randomization analysis - Chen, Yalan; Gao, Jie; Wang, Xibin; Lu, Hong; Zheng, Ya; Ren, Qian (Frontiers in Nutrition, 2024)
Evidence from observational studies on the association between folate and metabolic dysfunction-associated steatotic liver disease (MASLD) is conflicting.Aims: This study aimed to investigate the association between serum folate concentration and MASLD and further assess the causal relationship using Mendelian randomization (MR) analysis.To investigate the causal relationship between serum folate and MASLD, we conducted a cross-sectional study that selected 1117 participants from the 2017-2020 National Health and Nutrition Examination Survey (NHANES). The association between serum folate level and the risk of MASLD was evaluated under a multivariate logistic regression model.In addition, we conducted a two-sample MR Study using genetic data from a large genome-wide association study (GWAS) to compare serum folate level (37465 individuals) and MASLD (primary analysis: 8434 cases/770180 controls; Secondary analysis:1483 cases/17781 controls) were performed to infer causal relationships between them. Inverse variance weighted (IVW) was used as the primary method of MR Analysis.The results from the NHANES database showed that Tertile 3 group (Tertile 3: ≥ 48.6 nmol/L) had a significantl y lower risk (OR=0.58, 95% CI: 0.38 ~ 0.88, P=0.010) of MASLD than Tertile 1 group (Tertile 1: < 22.3 nmol/L) after co mplete adjustments. However, in the IVW of MR Analysis, there was no causal relationship between serum folate level a nd MASLD risk in the primary analysis (OR=0.75, 95% CI:0.55~1.02, P=0.065) and secondary analysis (OR=0.83, 95% CI: 0.39~1.74, P=0.618).In observational analyses, we observed an inverse association between higher serum folate concentrations and a reduced risk of MASLD. Our MR study generated similar results, but the association failed to reach the significance threshold of P<0.05, suggesting that our MR study does not support a causal relationship between serum folate levels and MASLD risk. Additional research involving a larger number of cases would contribute to enhancing the confirmation of our preliminary findings.